Effect of ohmic-drop on electrochemical performance of EDLC fabricated from PVA:dextran:NH4I based polymer blend electrolytes - Aziz, Shujahadeen B.; Brza, Mohamad A.; M. H., Hamsan; M.F.Z., Kadir; Muzakir, Saifful K.; Abdulwahid, Rebar T. (Elsevier Ltd, 2020)
Proton conducting solid polymer blend electrolytes based on poly(vinyl alcohol)(PVA):dextran that were doped with different quantities of ammonium iodide (NH4I) were prepared. The X-ray diffraction (XRD) and Fourier-transform infrared (FTIR) study were carried out to examine the compatibility of NH4I withPVA:dextran polymers. FTIR spectroscopy assessment was used to establish the presence of a complex formation between the PVA:dextran and added salt through the modification and reduction in the intensity of FTIR bands relevant to the functional groups. The field emission scanning electron microscopy (FESEM) examination was used to assess the channels for proton transport. Electrical impedance spectroscopy (EIS) was used to analyse the samples conductivity behaviour. The sample with 20 wt.% of added salt has shown a high DC conductivity which can be employed in electrochemical devices such as EDLC. It is also demonstrated by the transference number (TNM) and linear sweep voltammetry (LSV) that it is appropriate to use the largest conducting sample for electrochemical device. There was electrochemical stability of the electrolyte sample with voltage sweeping linearly to 1.3 V. It is shown by the outcome of cyclic voltammetry (CV) plot that charge storage at the site of electrode-electrolyte is non-Faradiac. A high drop voltage (Vd=IR) is implied by the usual galvanostatic charge-discharge. The equivalent series resistance (Res) increases as a result of the increase in Vd all the way through the charge-discharge cycle. Specific capacitance (Csp) is nearly constant from the foremost cycle to the 100th cycle, with average of 4.2 F/g.